Pulmonary Artery Size Measurements: A Comparison Study Between Electrocardiogram-Gated and Nonelectrocardiogram-Gated Computed Tomography. Issue 3 (May 2021) - Li, Danyan; Tang, Xin; Zhu, Yinsu; Wei, Yongyue; Mu, Dan
Abstract : Objectives: The aim of this study was to determine the difference and correlation in pulmonary artery (PA) size when measured from the electrocardiogram (ECG)–gated computed tomography (CT) and non–ECG-gated CT. Methods: In the retrospective study, 279 patients who underwent both ECG-gated CT and non–ECG-gated CT were enrolled. Maximum and minimum diameters of main pulmonary artery (MPA), right pulmonary artery (RPA), and ascending aorta (AAO) were measured, whereas mean diameters of MPA and RPA were obtained. The same PA size parameters were also measured on non–ECG-gated CT. Results: There was a significant difference in maximum and minimum PA diameters between ECG-gated CT and non-ECG-gated CT, whereas mean PA diameters showed no statistically difference. The PA parameters showed a strong positive correlation between these 2 examinations. Conclusions: The PA size was different between ECG-gated CT and non–ECG-gated CT, whereas the PA size parameters on non–ECG-gated CT could be used to predict those with ECG-gated CT, which allow for confident prediction of pulmonary hypertension and guide further surgical intervention.